Gamma irradiation sensitivity and optimal level for induction of mutation in tuberose (Polianthes tuberosa) - JYOTHI, R; SINGH, K P (The Indian Journal of Agricultural Sciences, 2015)
To evaluate the sensitivity, proper bulb stage and optimal gamma irradiation dosage to induce the attractive mutant in tuberose (Polianthes tuberose L.), a field experiment was conducted in 2008, 2009, 2010 and 2011 at the Indian Agricultural Research Institute, New Delhi. Cultivars Prajwal and Phule Rajani with three different bulb stages, viz. freshly harvested bulb (B0), three weeks after uprooting (B1) and six weeks after uprooting (B2) were irradiated by 2.5 Gy, 5.0 Gy, 7.5 Gy, 10.0 Gy and 15.0 Gy of gamma rays. Probable LD50 dose of gamma irradiation was between 10.0 Gy to 12.0 Gy for freshly harvested bulbs and bulbs after six weeks after uprooting in cv. Prajwal and in all the bulb stages of cv. Phule Rajani. For bulbs after three weeks after uprooting probable LD50 dose was 3.25 Gy in cv. Prajwal and 10.25 Gy in cv. Phule Rajani. Non sprouting of Prajwal bulbs at B1 stage beyond 2.5 Gy was supported by the histological results. The all three stages of bulbs have showed different response over gamma irradiation. In general, we have observed sprouting and all the vegetative parameters decreased over increased irradiation level. Out of three bulb stages tested, freshly harvested bulbs (B0) responded comparably high to the gamma irradiation doses followed by bulbs after six weeks of uprooting (B2) in both the tuberose cultivars. From this study, it was concluded that gamma irradiation dose 7.5 Gy to 11.5 Gy could yield some attractive and useful mutants in tuberose.